2008
DOI: 10.3146/ps06-039.1
|View full text |Cite
|
Sign up to set email alerts
|

Herbicide Systems for Control of Horse Purslane (Trianthema portulacastrum L.), Smellmelon (Cucumis melo L.), and Palmer Amaranth (Amaranthus palmeri S. Wats) in Peanut

Abstract: Field studies were conducted during the 2003 through 2005 growing seasons to evaluate soilapplied herbicides alone or in combination with postemergence (POST) herbicides for horse purslane, smellmelon, and Palmer amaranth control in peanut. Pendimethalin alone applied preplant incorporated (PPI) failed to control any of the three weeds (, 70% control). Pendimethalin in combination with diclosulam, followed by imazethapyr applied preemergence (PRE), or followed by either acifluorfen or imazapic applied postemer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
28
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 17 publications
1
28
0
Order By: Relevance
“…Also, the lactofen product label requires that sequential applications be made at least 14 DAIT, possibly because the level of control does not improve when applied at a shorter interval (Anonymous 2015). Although studies have shown lactofen to have higher activity on Palmer amaranth than acifluorfen, bentazon, or 2,4-DB, many of these studies did not investigate the recovery of Palmer amaranth over time (Grichar 1997a(Grichar , 2008Mayo et al 1995). Gaeddert et al (1997) did record Palmer amaranth control over time and found that acifluorfen and lactofen provided the same level of control 7 d after treatment, but by 28 d after treatment lactofen provided 16% more control than acifluorfen.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Also, the lactofen product label requires that sequential applications be made at least 14 DAIT, possibly because the level of control does not improve when applied at a shorter interval (Anonymous 2015). Although studies have shown lactofen to have higher activity on Palmer amaranth than acifluorfen, bentazon, or 2,4-DB, many of these studies did not investigate the recovery of Palmer amaranth over time (Grichar 1997a(Grichar , 2008Mayo et al 1995). Gaeddert et al (1997) did record Palmer amaranth control over time and found that acifluorfen and lactofen provided the same level of control 7 d after treatment, but by 28 d after treatment lactofen provided 16% more control than acifluorfen.…”
Section: Resultsmentioning
confidence: 99%
“…For mid-season application, the only other effective herbicides are the PPO-inhibitors. Palmer amaranth is adequately controlled by PPO-inhibiting herbicides when plants are less than 10 cm tall, but control declines quickly as plants surpass 10 cm in height (Gaeddert et al 1997;Grichar 2007Grichar , 2008Grichar and Dotray 2011;Mayo et al 1995;Morichetti et al 2012). If applied when plants are taller than 10 cm, most PPO-inhibiting herbicides control Palmer amaranth for 1 to 2 wk after treatment, but plants do not completely die and regrowth occurs (Morichetti et al 2012).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequent new growth did not show the effects of the lactofen applications and was 2% or less four wks after application (data not shown). Other studies have reported that lactofen injury is transient and subsequent growth does not show any effects of the herbicide (Grichar, 2007;2008;Grichar and Dotray, 2011). Weed Control.…”
Section: Resultsmentioning
confidence: 99%
“…Postemergence applications of imazapic, lactofen, lactofen plus S-metolachlor, or lactofen plus acetochlor included a crop oil concentrate (Agridex, Helena Chemical Co., Memphis, TN 38119) at 1% (v/v) at both locations. The pendimethalin followed by imazapic treatment was included because it is a commercial standard in many peanut growing areas of the state (Grichar 2007;2008). An non-treated check was also included at both locations.…”
mentioning
confidence: 99%